2013
DOI: 10.4304/jltr.4.6.1184-1190
|View full text |Cite
|
Sign up to set email alerts
|

Absenteeism and Language Learning: Does Missing Class Matter?

Abstract: Abstract-In a word, yes. The study determined the relationship between class attendance and mastery of a second language. Instructors kept detailed records of both attendance and classroom-discussed material. In a content-based class, the in-class material exam questions were isolated and the results showed that missing a single class increased the student's likelihood of an incorrect answer by three times compared to a student who attended class when the material was discussed. In a skills-based class, where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The urgency of class attendance is even highlighted in the foreign language learning context, where the classroom is typically the sole place of students' exposure to the target language (Pishghadam et al, 2019). This claim was also confirmed by previous research evidence showing that class absenteeism negatively influences students' language learning (Fay et al, 2013). Among the many factors impacting students' WTAC, teacher quality has been found to play an indispensable role in students' decision to attend classes or not (Gershenson, 2016).…”
Section: Literature Reviewsupporting
confidence: 78%
“…The urgency of class attendance is even highlighted in the foreign language learning context, where the classroom is typically the sole place of students' exposure to the target language (Pishghadam et al, 2019). This claim was also confirmed by previous research evidence showing that class absenteeism negatively influences students' language learning (Fay et al, 2013). Among the many factors impacting students' WTAC, teacher quality has been found to play an indispensable role in students' decision to attend classes or not (Gershenson, 2016).…”
Section: Literature Reviewsupporting
confidence: 78%
“…It is widely accepted that an effective EFL class will include inter-learner communication in group or pair work (Richards & Rodgers, 2001;Brown, 2001) and also needs clear and concise communication between the students and the teacher (Swain, 2005;Ellis, 2008). Furthermore, previous research (Fay, Aguirre, & Gash, 2013;Hamamcı & Hamamcı, 2017) has shown there is a relationship between consistent student attendance and language learning performance. Clearly, having to wear a facemask, the restrictions on student interaction, and mandatory absences as a result of having to take a test and/or positive result is going to severely affect how both teachers and learners approach the post COVID EFL classroom.…”
Section: Introductionmentioning
confidence: 89%
“…Research on the link between attendance and foreign language achievement is rare (Fay, Aguirre & Gash 2013), but studies have found positive effects. Not surprisingly, researches that focused on this link have yielded positive links and effects.…”
Section: Prior Studies Relating Teacher Absences To Student Achievementmentioning
confidence: 99%